The factors in the decision-making of high school graduates about higher education in the digital era - Nailya Askarova; Olga Shalamova; Liia Voronova (International Journal of Evaluation and Research in Education (IJERE), 2024)
Numerous specialists from different fields and perspectives have investigated determinants affecting the choice of future career path by school-leavers. The present study aims to analyze the factors influencing the decision of applicants to choose an academic major at a higher educational institution in the context of the digitalization of education. The authors developed the questionnaire for interviewing respondents. The survey involved a total of 160 students from Russia and Kazakhstan. The study took place from September to November 2022. The researchers collected a large amount of data, including the average scores of students and first-year students’ responses to the survey. The analysis of these data revealed many factors that influence a school graduate’s decision on a future academic major. The results describe three groups of factors that influenced the students’ decisions, namely family, social, and academic ones. The findings suggest that students choose an academic major more independently when they have an online learning experience. In the context of digitalized education, respondents are more likely to discuss their profession with peers or friends in social networks than with parents (0.49 vs. 0.31).